Microbial soluble aromatic prenyltransferases for engineered biosynthesis - He-Ping Chen; Ikuro Abe (Synthetic and Systems Biotechnology, 2021)
Prenyltransferase (PTase) enzymes play crucial roles in natural product biosynthesis by transferring isoprene unit(s) to target substrates, thereby generating prenylated compounds. The prenylation step leads to a diverse group of natural products with improved membrane affinity and enhanced bioactivity, as compared to the non-prenylated forms. The last two decades have witnessed increasing studies on the identification, characterization, enzyme engineering, and synthetic biology of microbial PTase family enzymes. We herein summarize several examples of microbial soluble aromatic PTases for chemoenzymatic syntheses of unnatural novel prenylated compounds.